Bevacizumab Demonstrates Prolonged Disease Stabilization in Patients with Heavily Pretreated Metastatic Renal Cell Carcinoma: A Case Series and Review of the Literature - Nicole M. Agostino; Rebecca Gingrich; Joseph J. Drabick (Advances in Urology)
There are now a variety of therapies approved for the treatment of metastatic renal cell carcinoma (RCC). These include the immunotherapeutics, alfa-interferon, and interleukin-2, and agents that target the vascular endothelial growth factor receptor (VEGFR) via its tyrosine kinase, such as sorafenib, sunitinib, and pazopanib, or the mammalian target of rapamycin (mTOR), such as temsirolimus and everolimus. Bevacizumab, a monoclonal antibody directed against the ligand, VEGF, has shown activity against RCC as a single agent in patients who had failed prior cytokine therapy and as first line therapy in combination with interferon. The activity of bevacizumab in patients who had received and failed prior therapy has not been described. We report our experience in 4 patients with metastatic RCC who had failed prior cytokine, TKI, and mTOR inhibitors who were treated with bevacizumab as single agent therapy. These heavily pretreated patients sustained very prolonged periods of stable disease (median of 12 months) with very little toxicity and excellent quality of life. The activity of this agent in patients who had failed prior therapies directed against the VEGFR and mTOR suggests that therapy targeting the ligand, VEGF, is still a viable approach in these patients and deserves further study.